Regionalism from Islamic views: the case of the Middle East and North Africa (Mena) region - Bendebka, Ramzi (Academic Inspired Network, 2019)
Regional experiences have certain assumptions in common and have been framed within a common globalist perspective. Nevertheless, each regional cooperation process has its own distinctive features. This diversity reflects the differential local characteristics of regionalism which need to be included in any discussion about the subject. The case of the Middle East and North Africa region (MENA) stands out clearly in this context. This study addresses two major research questions. Firstly, what is the Islamic perspective on regional cooperation? secondly, is there any role of Islam in reshaping MENA’s regional cooperation? The objectives are to investigate the Islamic perspective of regional cooperation with regard to MENA and to examine the role of Islam in shaping MENA’s cooperation. This study uses Islamic perspective and regional cooperation as its conceptual framework. It is found that despite some positive motives of regionalism, MENA suffers from poor regionalism. It is characterised by slow and weak regional cooperation process and the absence or less dependency on Islamic values. On the other hand, the dependence of MENA on the political processes and economic development of the West; conflicts and weak governance; and the suffering in promoting a collective identity have continued to preserve the MENA region as an under-developed, less integrated and poorly cohesive regional unit.